PENGARUH DISKON DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA CV. MITRA CAHAYA NAULI PANDAN - Ratih Simanungkalit; Nelly A.Sinaga; Jeniusman Hutagalung (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2023)
The purpose of this study was to determine the effect of discounts and services, both individually and simultaneously on customer satisfaction at CV. Nauli Pandan Light Partners. The hypothesis in this study is that discounts have a positive effect on consumer satisfaction at CV. Nauli Pandan Light Partners. Services have a positive effect on consumer satisfaction at CV. Nauli Pandan Light Partners. Discounts and services simultaneously have a positive effect on consumer satisfaction at CV. Nauli Pandan Light Partners. The type of research used in this research is descriptive correlational research. Total population of 198 people. sample used as much as 25% of the population totaling 50 people. Source of data comes from primary and secondary data. Data were analyzed using descriptive analysis and quantitative analysis. The results of the study found that partially the discount variable had an effect on consumer satisfaction, where the t-count value was 2.900 > t-table value 2.008 or significant (Sig-t) of 0.006 < α (0.05). Partially the most dominant service variable influences consumer satisfaction, where the t-count value is 4.257 > ttable value 2.008 or significant (Sig-t) of 0.000 <α (0.05). Simultaneous test results obtained discounts and services simultaneously have a positive effect on consumer satisfaction, where Fcount (28.424) is greater than Ftable (3.18) or (28.424 > 3.18). The results of the calculation of the R Square determination coefficient of 0.528 means that 52.8% discount and service can affect consumer satisfaction, while the remaining 47.2% can be influenced by other factors not discussed in this study. Based on the multiple linear regression model, the regression equation is Y = 4.069 + 0.346 X1 + 0.540 X2 indicating consumer satisfaction in a positive direction.